2018
DOI: 10.1016/j.epidem.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

An infectious way to teach students about outbreaks

Abstract: HighlightsAn updated epidemiological teaching exercise was developed.Students participate in an outbreak that they subsequently analyse.Data from five years of consecutive student cohorts is presented.An R package and practical are developed that improve the pedagogical experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…They found that an attack rate of 93% was approximately equal to the expected theoretical attack rate if R 0 = 2.85 [22]. In addition, Cremin I presented a teaching exercise in which an infectious disease outbreak was simulated over a five-day period and found substantial variation in the cumulative attack rate, with between 26 and 83% of the students uninfected at the end of each outbreak [23]. Although these studies employed the concept of individual-level and random contact among people, they did not fully account for certain factors, such as differences in patient contact behaviour during day and night, the time of isolation, and the duration from onset to isolation, which influences morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…They found that an attack rate of 93% was approximately equal to the expected theoretical attack rate if R 0 = 2.85 [22]. In addition, Cremin I presented a teaching exercise in which an infectious disease outbreak was simulated over a five-day period and found substantial variation in the cumulative attack rate, with between 26 and 83% of the students uninfected at the end of each outbreak [23]. Although these studies employed the concept of individual-level and random contact among people, they did not fully account for certain factors, such as differences in patient contact behaviour during day and night, the time of isolation, and the duration from onset to isolation, which influences morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cremin I presented a teaching exercise in which an infectious disease outbreak was simulated over a five-day period and found 5 substantial variation in the cumulative attack rate, with between 26% and 83% of the students uninfected at the end of each outbreak. [23]. Although these studies employed the concept of individual-level and random contact among people, they did not fully account for certain factors, such as differences in patient contact behaviour during day and night, the time of isolation, and the duration from onset to isolation, which influences morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cremin I presented a teaching exercise in which an infectious disease outbreak is simulated over a five-day period and found there was substantial variation in the cumulative attack rate, with between 26% and 83% of the students uninfected at the end of each outbreak. [22]. Although these studies employed the concept of individual-level and random contact among people, they did not fully account for certain factors, such as the difference in patient contact behaviour during the day and at night, the time of isolation, and the duration from onset to isolation, which influences morbidity.…”
Section: Introductionmentioning
confidence: 99%